An electro-Fenton cathode material and its preparation method and application
The electrofenton cathode material modified by phosphoric acid and synergistic hydroxylated carbon nanotubes has been solved, and the problem of low hydrogen peroxide production in the prior art is achieved efficiently degrading COD and color in the printing and dyeing wastewater, meeting emission standards, and having good activity and stability.
Patent Information
- Application Number
- CN202510106246.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The existing electrofenton cathode materials have low hydrogen peroxide production when treating printing and dyeing wastewater, resulting in limited ability to oxidize and degrade organic pollutants.
The electrofenton cathode material modified by phosphoric acid synergistic hydroxylated carbon nanotubes is used to adjust the phosphoric acid doping concentration and calcining temperature in the modification process through hydrothermal reaction and calcination treatment, and improve the activity and stability of the material.
It achieves efficient in-situ generation of hydrogen peroxide, with a accumulation of up to 280.64 mg/L, which can efficiently degrade COD and color in reverse osmosis concentrated water, meet the emission standards of printing and dyeing wastewater, and have the stability of repeated recycles.
Smart Images

Figure CN119551772B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electro-Fenton cathode materials, and in particular to an electro-Fenton cathode material modified by phosphoric acid-synergistic hydroxylated carbon nanotubes, and a preparation method and application thereof. Background Art
[0002] With the development of industry in recent years, the types and concentrations of organic pollutants in printing and dyeing wastewater have become increasingly complex. Among them, chemical oxygen demand (COD) and chromaticity mainly come from organic matter such as dyes, auxiliaries and cellulose that are not used in the printing and dyeing process. If it is discharged directly without proper treatment, it will seriously pollute the water environment.
[0003] The commonly used advanced treatment process for printing and dyeing wastewater currently includes physical and chemical pretreatment - biochemical treatment - membrane treatment (nanofiltration / reverse osmosis) - flocculation / advanced oxidation treatment. Among them, the electro-Fenton process is one of the advanced oxidation processes for treating wastewater with medium and low organic concentrations. This technology uses Fe generated by electrochemical method to 2+ With H2O2 as a continuous source of Fenton's reagent, less sludge is produced, and the operation and post-treatment during the electrolysis process are simple. It is a treatment method with strong oxidation ability and low energy consumption.
[0004] In the electro-Fenton system, the performance and stability of in-situ generated hydrogen peroxide are the criteria for judging whether the cathode material is valuable. By regulating the surface properties of the cathode material, the effect of the electro-Fenton reaction can be improved and the treatment cost of printing and dyeing wastewater can be reduced. Therefore, the selection of suitable cathode materials and modification methods are currently hot topics of research at home and abroad.
[0005] As the cathode material of the electro-Fenton system, activated carbon fiber felt has the characteristics of high stability, large specific surface area, unchanged physical properties after sintering, and the ability to form active sites after activation. Many scholars have used activated carbon fiber felt as a substrate for processing and modification to improve the oxygen reduction performance of the electrode. However, the efficiency of ordinary activated carbon carbon fiber felt in producing hydrogen peroxide is low and needs to be improved.
[0006] In the prior art, for example, the Chinese patent document with application number 201711019400.7 discloses the preparation and application of an electro-Fenton cathode material based on supported activated carbon fiber. This method involves immersing pretreated activated carbon fiber in a complexing agent metal salt solution, and using the oxygen generated by electrolyzing water at the anode to generate H2O2 in situ. This technical solution claims to be able to effectively catalyze the decomposition of hydrogen peroxide to generate hydroxyl radicals. However, according to the concentration of the generated oxide in Example 1, the production of hydrogen peroxide after 120 minutes of reaction is only 182.7μM (6.2mg / L), which has the problem of low production. It can be foreseen that its ability to oxidize and degrade organic pollutants is also limited.
[0007] Another example is the Chinese patent document with application number 202410188347.7, which discloses a method for preparing a graphite felt-loaded coconut shell carbon electric Fenton cathode material and its application. The method uses a graphite felt material as a substrate, and uses an ultrasonic deposition method to immerse the pretreated graphite felt electrode in a mixed solution containing commercial coconut shell carbon. The dried sample is placed in a muffle furnace for calcination, and after cooling, a graphite felt-loaded commercial coconut shell carbon modified electrode material is obtained. The preparation process is relatively costly, and the H2O2 yield is only 30 mg / L under the optimal preparation process, which has the disadvantages of low yield.
[0008] Therefore, developing a new type of green and efficient electro-Fenton cathode material is of great practical significance. Summary of the invention
[0009] In view of the above technical problems and the shortcomings in the art, the present invention provides an electro-Fenton cathode material modified by phosphoric acid and hydroxylated carbon nanotubes, and a preparation method and application thereof. The raw materials are cheap and easily available, and the preparation process is simple and controllable. The material prepared by the method of the present invention is used as a cathode to efficiently prepare hydrogen peroxide. After 150 minutes of reaction, the accumulated amount of hydrogen peroxide can reach up to 280.64 mg / L. Furthermore, the material prepared by the method of the present invention is used as a cathode to achieve efficient degradation of COD and chromaticity in reverse osmosis concentrated water, meeting the discharge standard GB4287-2012 for printing and dyeing wastewater effluent, and the cathode material has excellent activity and stability and can be repeatedly recycled.
[0010] [1] A method for preparing an electro-Fenton cathode material modified by phosphoric acid-co-hydroxylated carbon nanotubes, comprising:
[0011] Step 1: immersing the activated carbon fiber felt in a phosphoric acid solution, placing it in a reactor for hydrothermal reaction, the hydrothermal reaction temperature is 100-220° C. (e.g., 140° C., 180° C., etc.), the hydrothermal reaction time is 9-18 hours (e.g., 12 hours, 15 hours, etc.), the reaction product is washed with deionized water until it is neutral and dried; the phosphoric acid solution is obtained by diluting 85wt% concentrated phosphoric acid with water, and the volume usage of 85wt% concentrated phosphoric acid in the phosphoric acid solution accounts for 5%-25% (e.g., 10%, 15%, 20%, etc.);
[0012] Step 2: calcining the product after drying in step 1 in a tubular furnace at a temperature of 500-800° C. (e.g., 600° C., 700° C., etc.) in an inert atmosphere, and obtaining a phosphoric acid-doped modified cathode material after cooling;
[0013] Step 3: mixing hydroxylated carbon nanotubes (CNTs), a binder and a solvent to obtain a dispersion;
[0014] Step 4: immersing the phosphoric acid-doped modified cathode material obtained in step 2 in the dispersion obtained in step 3, and drying the material after sufficient immersion;
[0015] Step 5: The product after the drying treatment in step 4 is calcined, and after cooling, the electro-Fenton cathode material modified by phosphoric acid and hydroxylated carbon nanotubes is obtained.
[0016] In step 1, the volume proportion of 85wt% concentrated phosphoric acid in the phosphoric acid solution is preferably 10wt%. Under preferred conditions, the obtained phosphoric acid cooperates with the hydroxylated carbon nanotube modified electro-Fenton cathode material to have better COD and chromaticity treatment effects.
[0017] In step 1, the hydrothermal reaction temperature is preferably 180° C. Under preferred conditions, the electro-Fenton cathode material modified by phosphoric acid and hydroxylated carbon nanotubes has better COD and chromaticity treatment effects.
[0018] In step 1, the hydrothermal reaction time is preferably 15 hours. Under preferred conditions, the obtained phosphoric acid and hydroxylated carbon nanotube modified electro-Fenton cathode material have better COD and chromaticity treatment effects.
[0019] In step 1, the ratio of the activated carbon fiber felt deposition area to the volume of the phosphoric acid solution can be 70-80 cm 2 :50mL, e.g. 72 cm 2 :50 mL, etc.
[0020] In step 2, the calcination temperature in the tubular furnace is preferably 700° C. Under the preferred conditions, the electro-Fenton cathode material modified by phosphoric acid and hydroxylated carbon nanotubes has better COD and chromaticity treatment effects.
[0021] In step 2, the calcination time in the tubular furnace can be 2 to 3 hours.
[0022] In step 2, the inert atmosphere of the present invention refers to a gas atmosphere that does not participate in the reaction, and for example, it may be a rare gas atmosphere such as argon.
[0023] In step 3, the binder can be selected from one or more of polytetrafluoroethylene emulsion, polyvinylidene fluoride, and polyvinylidene fluoride.
[0024] In step 3, the solvent may be a mixed solution of water and isopropanol. Further, in the solvent, the volume ratio of water to isopropanol may be 10:0.5-2, such as 10:1.
[0025] In step 3, the mass ratio of the hydroxylated carbon nanotubes to the binder can be 0.5-1.5:1-5, preferably 0.5-1:3-4, such as 1:4, etc. The electro-Fenton cathode material modified with phosphoric acid and hydroxylated carbon nanotubes obtained under the preferred and exemplary conditions has better COD and color treatment effects.
[0026] In step 3, the ratio of the mass of the hydroxylated carbon nanotubes to the volume of the solvent may be 1 g:10-12 mL, for example, 1 g:11 mL.
[0027] In step 4, the ratio of the mass of the hydroxylated carbon nanotubes in the dispersion to the deposited area of the activated carbon fiber felt in the phosphoric acid-doped modified cathode material can be 7-21 mg:1 cm 2 , for example 14 mg:1 cm 2 wait.
[0028] In step 5, the calcination temperature may be 220-420°C, such as 280°C, 360°C, etc.
[0029] In step 5, the calcination time may be 1 to 2 hours.
[0030] In step 5, the calcination atmosphere may be air.
[0031] [2] The electro-Fenton cathode material prepared by the preparation method described in [1], which is modified by phosphoric acid-synergistic hydroxylated carbon nanotubes.
[0032] [3] The application of the electro-Fenton cathode material modified by phosphoric acid-synergistic hydroxylated carbon nanotubes as described in [2] in the in-situ electrogeneration of H2O2 or the electro-Fenton process for the treatment of COD and color of printing and dyeing wastewater.
[0033] [4] A method for treating COD and chromaticity in printing and dyeing wastewater using an electro-Fenton process, wherein iron is used as an anode and the electro-Fenton cathode material modified by phosphoric acid and hydroxylated carbon nanotubes described in [2] is used as a cathode. Further, the printing and dyeing wastewater may be reverse osmosis (RO) concentrated water adjusted to acidity, the pH may be 2-6, further may be 3-5, the COD concentration may be 500-600 mg / L, and the chromaticity may be 2000-3000 degrees.
[0034] In the method for treating COD and chromaticity in printing and dyeing wastewater using an electro-Fenton process, the current for the electro-Fenton process treatment may be 0.15 to 0.3 A, such as 0.2 A, 0.25 A, etc.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1) The present invention adopts an electro-Fenton cathode material modified with phosphoric acid and hydroxylated carbon nanotubes prepared by a special modification process as an electrode, generates H2O2 in situ, and achieves high-yield preparation by adjusting parameters such as phosphoric acid doping concentration, hydrothermal reaction conditions, and tubular furnace calcination temperature in the modification process, with the highest yield reaching 280.64 mg / L.
[0037] 2) The present invention adopts an electro-Fenton cathode material modified with phosphoric acid and hydroxylated carbon nanotubes prepared by a special modification process as the cathode, and an iron plate as the anode. By using the electro-Fenton technology, the COD and chromaticity in the actual RO concentrated water of printing and dyeing wastewater are efficiently degraded without the need for an external flocculant, thereby meeting the discharge standard GB4287-2012 for printing and dyeing wastewater effluent.
[0038] 3) The electro-Fenton cathode material modified by phosphoric acid and hydroxylated carbon nanotubes prepared by the present invention has high activity and stability, and the electrode material can be repeatedly recycled. After being recycled for 4 times, the effluent of printing and dyeing wastewater still meets the discharge standard of printing and dyeing wastewater effluent GB4287-2012; after being recycled for 5 times, the COD removal rate in the wastewater can still reach more than 63%. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Part (a) is a scanning electron microscope (SEM) photograph of the electro-Fenton cathode material modified by phosphoric acid-synergistic hydroxylated carbon nanotubes prepared in Example 1. Figure 1 Part (b) is a SEM image of activated carbon fiber felt modified by phosphoric acid doping. Figure 1 Part (c) is the SEM image of the activated carbon fiber felt that has only been pretreated. Figure 1 Part (d) is the SEM image of hydroxylated carbon nanotubes.
[0040] Figure 2 This is a comparison chart of H2O2 production of the electro-Fenton cathode material modified with phosphoric acid and hydroxylated carbon nanotubes (P-ACF / CNTs-OH) prepared in Example 1, the activated carbon fiber felt electrode material modified by phosphoric acid doping (P-ACF), and the activated carbon fiber felt electrode material (unmodified) that has only been pretreated.
[0041] Figure 3 This is a graph showing the cyclic degradation efficiency of an electro-Fenton experiment on COD in reverse osmosis concentrate using the electro-Fenton cathode material modified with phosphoric acid and hydroxylated carbon nanotubes prepared in Example 1 as the cathode.
[0042] Figure 4 This is a diagram showing the degradation effect of COD and chromaticity in reverse osmosis concentrate under different pH conditions when an electro-Fenton experiment was carried out using the electro-Fenton cathode material modified with phosphoric acid and hydroxylated carbon nanotubes prepared in Example 1 as the cathode.
[0043] Figure 5 This is a diagram showing the degradation effect of COD and chromaticity in reverse osmosis concentrate under different current conditions when an electro-Fenton experiment was carried out using the electro-Fenton cathode material modified with phosphoric acid and hydroxylated carbon nanotubes prepared in Example 1 as the cathode.
[0044] Figure 6 The graph shows the degradation effect of COD and chromaticity in reverse osmosis concentrated water by the activated carbon fiber felt pretreated in Comparative Example 1 and the phosphoric acid-doped modified activated carbon fiber felt electrodes of Comparative Example 2 and Examples 12 to 15.
[0045] Figure 7 This is a diagram showing the degradation effects of the activated carbon fiber felt pretreated in Comparative Example 1 and the phosphoric acid-doped modified activated carbon fiber felt electrodes of Comparative Example 2 and Examples 16 to 18 on COD and chromaticity in reverse osmosis concentrate.
[0046] Figure 8 This is a diagram showing the degradation effects of the activated carbon fiber felt pretreated in Comparative Example 1 and the phosphoric acid-doped modified activated carbon fiber felt electrodes of Comparative Example 2 and Examples 19 to 21 on COD and chromaticity in reverse osmosis concentrate.
[0047] Fig. 9 This is a diagram showing the degradation effects of the activated carbon fiber felt pretreated in Comparative Example 1 and the phosphoric acid-doped modified activated carbon fiber felt electrodes of Comparative Example 2 and Examples 22 to 24 on COD and chromaticity in reverse osmosis concentrate.
[0048] Fig.10 This is a diagram showing the degradation effects of the electro-Fenton cathode materials of Examples 1 and 25 to 27 on COD and chromaticity in reverse osmosis concentrate. DETAILED DESCRIPTION
[0049] The present invention will be further described below in conjunction with the accompanying drawings and specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0050] Specific implementation method The reverse osmosis concentrated water of printing and dyeing wastewater used was taken from a textile industrial park in Keqiao, Shaoxing, Zhejiang Province. The main water quality indicators of the concentrated water of the printing and dyeing wastewater after ultrafiltration and reverse osmosis double membrane system are shown in Table 1.
[0051] Table 1
[0052]
[0053] Embodiment 1:
[0054] Step (1) is to place activated carbon fiber felt (size 6 cm × 6 cm × 0.2 cm, deposition area 72 cm2 ) were immersed in acetone, ethanol, and ultrapure water solution for ultrasonic cleaning for 20 min respectively. The SEM photos of the pretreated activated carbon fiber felt are shown in Figure 2. Figure 1 As shown in (c), it is immersed in 50 mL of a phosphoric acid solution of a certain concentration, the phosphoric acid solution is obtained by diluting 85 wt % concentrated phosphoric acid with water, and the volume ratio of 85 wt % concentrated phosphoric acid in the phosphoric acid solution is 10%, and then placed in a reactor for hydrothermal reaction, the hydrothermal reaction temperature is 180 ° C, the hydrothermal reaction time is 15 hours, and the hydrothermal reaction product is washed with deionized water to neutrality and dried.
[0055] Step (2), the activated carbon fiber felt obtained by drying in step (1) is placed in a tube furnace and calcined at a certain temperature for 2 h. The tube furnace calcination temperature is 700°C and the tube furnace calcination adopts an argon atmosphere to obtain a phosphoric acid doped modified activated carbon fiber felt electrode (P-ACF), the SEM photo of which is shown as follows: Figure 1 (b) shown.
[0056] Step (3), weigh 1 g of hydroxylated carbon nanotubes and 4 g of polytetrafluoroethylene emulsion, add them to a mixed solution containing 10 mL of ultrapure water and 1 mL of isopropanol, and ultrasonicate for 30 min to obtain a uniform hydroxylated carbon nanotube dispersion. The SEM image of the hydroxylated carbon nanotubes is shown in Figure 1 (d) shown.
[0057] Step (4), immersing the phosphoric acid-doped modified activated carbon fiber felt electrode obtained in step (2) in the hydroxylated carbon nanotube dispersion obtained in step (3), and then evenly applying the excess dispersion to the surface and drying.
[0058] Step (5), placing the dried product obtained in step (3) in a muffle furnace and calcining it in an air atmosphere at 360°C for 1 hour, cooling it to room temperature, and obtaining an electro-Fenton cathode material modified by phosphoric acid and hydroxylated carbon nanotubes, as shown in the SEM photograph. Figure 1 (a) shown.
[0059] H2O2 accumulation test:
[0060] An aluminum plate was used as the anode, the electro-Fenton cathode material modified with phosphoric acid and hydroxylated carbon nanotubes prepared in Example 1 was used as the cathode, water was used as the electrolyte, hydrochloric acid was added to adjust the pH to 3.0, NaCl was added to make its concentration 0.15 mol / L, oxygen was continuously introduced near the cathode, and the H2O2 production test was carried out under the condition of current I=0.2 A.
[0061] According to the test, after 120 min of reaction, the accumulated amount of H2O2 can reach 280.64 mg / L. Figure 2 .like Figure 2As shown, in Example 1, the activated carbon fiber felt electrode material (unmodified) that had only been pretreated and the activated carbon fiber felt electrode material (P-ACF) that had been modified by doping with phosphoric acid were tested under the same conditions. After 120 minutes of reaction, the accumulated amounts of H2O2 were only 7.8197 mg / L and 10.8125 mg / L, respectively.
[0062] Application performance testing:
[0063] The iron plate was used as the anode, and the electro-Fenton cathode material modified with phosphoric acid and hydroxylated carbon nanotubes prepared in Example 1 was used as the cathode. Hydrochloric acid was added to adjust the pH of the reverse osmosis concentrate to 3.0, oxygen was continuously introduced near the cathode, and the electro-Fenton experiment was carried out under the condition of current I=0.2 A.
[0064] After 150 min of electro-Fenton treatment, the removal effects of COD and chromaticity met the discharge standard for printing and dyeing wastewater (GB4287-2012).
[0065] observe Figure 3 It can be found that after four cycle tests, the COD removal rate reached 65%, and the effluent met the discharge standards; after five cycle tests, the COD removal rate could still reach more than 63%, indicating that the modified cathode has good stability.
[0066] Comparative Example 1:
[0067] The activated carbon fiber felt (size 6 cm × 6 cm × 0.2 cm, deposition area 72 cm) was placed on the 2 ) were immersed in acetone, ethanol and ultrapure water solution for ultrasonic cleaning for 20 min respectively and then placed in a vacuum drying oven to obtain the pretreated activated carbon fiber felt.
[0068] Comparative Example 2:
[0069] Referring to step (1) and step (2) of Example 1, a phosphoric acid-doped modified activated carbon fiber felt electrode (P-ACF) was obtained.
[0070] Comparative Example 3:
[0071] Referring to step (1) and step (2) of Example 1, the only difference is that 50 mL of 10 wt % boric acid solution is used instead of phosphoric acid solution to obtain a boric acid-doped modified activated carbon fiber felt electrode.
[0072] Comparative Example 4:
[0073] Referring to step (1) and step (2) of Example 1, the only difference is that 50 mL of 10 wt % urea solution is used instead of the phosphoric acid solution to obtain a urea-doped modified activated carbon fiber felt electrode.
[0074] Application performance testing:
[0075] The same conditions as those of the above-mentioned test example 1 (pH=3.0) were adopted, and the activated carbon fiber felt prepared in comparative example 1 and the modified activated carbon fiber felts prepared in comparative examples 2, 3, and 4 were used as cathodes for testing.
[0076] After testing, when the phosphoric acid modified activated carbon fiber felt prepared in Comparative Example 2 was used as the cathode, the COD and chromaticity degradation rates were 44.65% and 91.89% respectively after 150 minutes of electro-Fenton treatment; when the boric acid modified activated carbon fiber felt prepared in Comparative Example 3 was used as the cathode, the COD and chromaticity degradation rates were 31.73% and 85.90% respectively after 150 minutes of electro-Fenton treatment; when the urea modified activated carbon fiber felt prepared in Comparative Example 4 was used as the cathode, the COD and chromaticity degradation rates were 30.63% and 89.73% respectively after 150 minutes of electro-Fenton treatment; and when the activated carbon fiber felt prepared in Comparative Example 1 was used as the cathode, the COD and chromaticity degradation rates were 25.65% and 90.52% respectively after 150 minutes of electro-Fenton treatment.
[0077] Comparative Example 5:
[0078] Referring to Example 1, the only difference is that the hydroxylated carbon nanotubes are replaced by carbon nanotubes of equal mass to obtain an electro-Fenton cathode material modified by phosphoric acid and carbon nanotubes.
[0079] Comparative Example 6:
[0080] Referring to Example 1, the only difference is that the hydroxylated carbon nanotubes are replaced by the same mass of carboxylated carbon nanotubes to obtain the electro-Fenton cathode material modified by phosphoric acid and carboxylated carbon nanotubes.
[0081] The application performance test was carried out under the same conditions (pH=3.0) as in the above test example 1, except that the cathode was replaced with the electro-Fenton cathode materials prepared in comparative examples 5 and 6, respectively. The test results are listed in Table 2 below.
[0082] Table 2
[0083]
[0084] As can be seen from Table 2, the activated carbon fiber felt modified with carbon nanotubes, hydroxylated carbon nanotubes, and carboxylated carbon nanotubes can effectively promote the degradation of COD compared with the activated carbon fiber felt electrode modified with phosphoric acid alone. However, only the effluent concentrations of COD and chromaticity in the wastewater treated with the electrode modified with phosphoric acid and hydroxylated carbon nanotubes can meet the "Textile Dyeing and Finishing Industry Water Pollution Emission Standard" GB4287-2012 (which stipulates that the COD emission is less than 200 mg / L and the chromaticity emission is less than 80 degrees).
[0085] Embodiment 2~4:
[0086] The preparation process is basically the same as that of Example 1, except that the mass of the hydroxylated carbon nanotubes in step (3) is replaced by 0 g, 0.50 g, and 1.50 g, respectively.
[0087] The same conditions as in Example 1 (pH=3.0) were used to test the accumulation of H2O2, except that the cathode was replaced with the electro-Fenton cathode materials prepared in Examples 2 to 4, respectively. The accumulation of H2O2 within 150 min is shown in Table 3 below.
[0088] Table 3
[0089]
[0090] The same application performance test conditions as in Example 1 (pH=3.0) were used, with the only difference being that the cathode was replaced with the electro-Fenton cathode materials prepared in Examples 2 to 4, respectively. The test results are listed in Table 4 below.
[0091] Table 4
[0092]
[0093] As can be seen from Table 4, the change in the content of hydroxylated carbon nanotubes has a greater impact on COD removal and a smaller impact on chromaticity removal. Based on the analysis of the changes in the above data, it may be that when the content of hydroxylated carbon nanotubes increases, the content of CNTs as electron transfer carriers also increases, which is conducive to the efficient reaction; but when the loading reaches a certain value, the side reactions of the system increase, consuming hydroxyl radicals (·OH), resulting in a decrease in degradation rate.
[0094] Embodiment 5~8:
[0095] The preparation process is basically the same as that of Example 1, except that the mass of the polytetrafluoroethylene emulsion in step (3) is replaced with 1 g, 2 g, 3 g and 5 g respectively.
[0096] The accumulation of H2O2 was tested under the same conditions as in Example 1 (pH=3.0), except that the cathode was replaced with the electro-Fenton cathode materials prepared in Examples 5 to 8, respectively. The accumulation of H2O2 within 150 min is shown in Table 5 below.
[0097] Table 5
[0098]
[0099] The same application performance test conditions as those in Example 1 (pH=3.0) were used, with the only difference being that the cathode was replaced with the electro-Fenton cathode materials prepared in Examples 5 to 8, respectively. The test results are shown in Table 6.
[0100] Table 6
[0101]
[0102] It can be seen from Tables 5 and 6 that when the mass ratio of hydroxylated carbon nanotubes to polytetrafluoroethylene emulsion is 1:4, the accumulation of H2O2 is the largest and COD removal is the best. Based on the analysis of the changes in the above data, the increase in polytetrafluoroethylene content can increase the hydrophobicity of the electrode material and promote the generation of H2O2; however, too much PTFE will make the electrode too hydrophobic, affecting the effective contact area between the solution and the electrode, causing excessive dispersion of O2, reducing the conductivity of the electrode, and increasing energy consumption.
[0103] Embodiment 9-11:
[0104] The preparation process is basically the same as that of Example 1, except that the calcination temperature in step (5) is replaced with 220°C, 280°C, and 420°C in sequence.
[0105] The accumulation of H2O2 was tested under the same conditions as in Example 1 (pH=3.0), except that the cathode was replaced with the electro-Fenton cathode materials prepared in Examples 9 to 11, respectively. The accumulation of H2O2 within 150 min is shown in Table 7.
[0106] Table 7
[0107]
[0108] The same application performance test conditions as in Example 1 (pH=3.0) were adopted, with the only difference being that the cathode was replaced with the electro-Fenton cathode materials prepared in Examples 9 to 11, respectively. The test results are shown in Table 8.
[0109] Table 8
[0110]
[0111] The experiment found that the calcination temperature mainly affects the film-forming properties of polytetrafluoroethylene. Too high a temperature may damage the film structure, the hydroxylated carbon nanotubes cannot be stably loaded on the carbon felt, the H2O2 production decreases, and the COD removal effect also decreases.
[0112] Application performance testing:
[0113] 1. The electro-Fenton cathode material modified by phosphoric acid and hydroxylated carbon nanotubes prepared in Example 1 was used as the cathode. The same test conditions as in Example 1 were used, except that the pH values of the reverse osmosis concentrate to be treated were adjusted to 2, 4, 5 and 6, respectively. The degradation of COD and chromaticity in the reverse osmosis concentrate with different pH values was as follows: Figure 4 shown.
[0114] Depend on Figure 4 It can be seen that strong acidic conditions (pH=2) are not conducive to the removal of COD and chroma. When pH≥3, the COD removal effect decreases with the increase of pH. When pH=3, the COD removal rate reaches 65% after 150 min of treatment.
[0115] 2. The electro-Fenton cathode material modified with phosphoric acid and hydroxylated carbon nanotubes prepared in Example 1 was used as the cathode. The same test conditions as in Example 1 were used, except that the current of the electro-Fenton treatment was adjusted to 0.1 A, 0.15 A, and 0.25 A, respectively. The degradation of COD and chromaticity in the reverse osmosis concentrate under different currents was shown in FIG. Figure 5 shown.
[0116] Depend on Figure 5 It can be seen that the removal effect of COD and chromaticity increases with the increase of current. When the current is too low, the power consumption is small, but the pollutant effluent concentration does not meet the emission standards; when the current is too large, the pollutants can be quickly degraded, but the power consumption is high and the treatment cost is high. The preferred current is 0.2 A.
[0117] Embodiment 12-15:
[0118] Referring to step (1) and step (2) of Example 1, the volume ratio of 85 wt % concentrated phosphoric acid in the phosphoric acid solution was changed to 5%, 15%, 20% and 25% respectively, to obtain the phosphoric acid-doped modified activated carbon fiber felt electrodes of Examples 12 to 15.
[0119] The phosphoric acid doped modified activated carbon fiber felt electrodes of Examples 12 to 15 were subjected to the same application performance test as in Example 1, and compared with the activated carbon fiber felt (unmodified) pretreated in Comparative Example 1 and the phosphoric acid doped modified activated carbon fiber felt electrode (10% P-ACF) in Comparative Example 2. The COD removal rate test results are shown in Figure 6 , showing that the optimal volumetric usage of 85wt% concentrated phosphoric acid in the phosphoric acid solution is 10%.
[0120] Embodiment 16-18:
[0121] Referring to step (1) and step (2) of Example 1, the hydrothermal reaction temperature was changed to 100° C., 140° C., and 220° C., respectively, to obtain the phosphoric acid-doped modified activated carbon fiber felt electrodes of Examples 16 to 18.
[0122] The phosphoric acid doped modified activated carbon fiber felt electrodes of Examples 16 to 18 were subjected to the same application performance test as in Example 1, and compared with the activated carbon fiber felt pretreated in Comparative Example 1 (PACF-0) and the phosphoric acid doped modified activated carbon fiber felt electrode (PACF-180°C) in Comparative Example 2. The COD removal rate and decolorization rate test results are shown in Figure 7 , showing that the hydrothermal reaction temperature is 180℃.
[0123] Embodiments 19-21:
[0124] Referring to step (1) and step (2) of Example 1, the hydrothermal reaction time was changed to 9 hours, 12 hours, and 18 hours, respectively, to obtain the phosphoric acid-doped modified activated carbon fiber felt electrodes of Examples 19 to 21.
[0125] The phosphoric acid doped modified activated carbon fiber felt electrodes of Examples 19 to 21 were subjected to the same application performance test as in Example 1, and compared with the activated carbon fiber felt pretreated in Comparative Example 1 (PACF-0) and the phosphoric acid doped modified activated carbon fiber felt electrode (PACF-15h) in Comparative Example 2. The COD removal rate and decolorization rate test results are shown in Figure 8 , showing that the hydrothermal reaction time of 15 hours is the best.
[0126] Embodiment 22-24:
[0127] Referring to step (1) and step (2) of Example 1, the calcination temperature in the tubular furnace was changed to 500° C., 600° C., and 800° C., respectively, to obtain the phosphoric acid-doped modified activated carbon fiber felt electrodes of Examples 22 to 24.
[0128] The phosphoric acid doped modified activated carbon fiber felt electrodes of Examples 22 to 24 were subjected to the same application performance test as in Example 1, and compared with the activated carbon fiber felt pretreated in Comparative Example 1 (PACF-0) and the phosphoric acid doped modified activated carbon fiber felt electrode (PACF-700) in Comparative Example 2. The COD removal rate and decolorization rate test results are shown in Table 1. Fig. 9 , showing that the best calcination temperature in a tubular furnace is 700°C.
[0129] Embodiment 25:
[0130] Referring to Example 1, the only difference is that phosphoric acid is not used, that is, the activated carbon fiber felt pretreated in step (1) is immersed in water for hydrothermal reaction, and the rest is the same to obtain an electro-Fenton cathode material, denoted as ACF-HT / CNTs-OH.
[0131] Embodiment 26:
[0132] Referring to steps (3) to (5) of Example 1, the only difference is that in step (4), the activated carbon fiber felt pretreated in step (1) of Example 1 is used to replace the phosphoric acid-doped modified activated carbon fiber felt electrode obtained in step (2), thereby obtaining an electro-Fenton cathode material, which is recorded as ACF / CNTs-OH.
[0133] Embodiment 27:
[0134] Referring to step (3) to step (5) of Example 1, the only difference is that in step (4), the phosphoric acid-doped modified activated carbon fiber felt electrode obtained in step (2) is replaced with activated carbon fiber felt impregnated with phosphoric acid solution and dried to obtain an electro-Fenton cathode material, which is recorded as P-ACF / CNTs-OH. The activated carbon fiber felt impregnated with phosphoric acid solution and dried is obtained by the following process: first, referring to step (1) of Example 1, obtain the pretreated activated carbon fiber felt, and then immerse it in 50 mL of a phosphoric acid solution of a certain concentration, wherein the phosphoric acid solution is obtained by diluting 85 wt% concentrated phosphoric acid with water, and the volume usage of 85 wt% concentrated phosphoric acid in the phosphoric acid solution accounts for 10%, and after immersion for 15 hours, take it out and dry it.
[0135] The electro-Fenton cathode materials of Examples 25 to 27 were subjected to the same application performance test as that of Example 1, and compared with the electro-Fenton cathode material (PACF-HT / CNTs-OH) of Example 1. The COD removal rate and decolorization rate test results are shown in Fig.10 , showing that the electro-Fenton cathode material of Example 1 is the best, and phosphoric acid impregnation and hydrothermal reaction have a synergistic effect.
[0136] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for treating COD and chromaticity in printing and dyeing wastewater using an electro-Fenton process, characterized in that: The method for treating COD and chromaticity in printing and dyeing wastewater by using an electro-Fenton process uses iron as an anode and an electro-Fenton cathode material modified by phosphoric acid and hydroxylated carbon nanotubes as a cathode; The printing and dyeing wastewater is reverse osmosis concentrated water adjusted to acidity, with a pH of 2-6, a COD concentration of 500-600 mg / L, and a chromaticity of 2000-3000 degrees; The preparation method of the electro-Fenton cathode material modified by phosphoric acid and hydroxylated carbon nanotubes comprises: Step 1: immerse the activated carbon fiber felt in a phosphoric acid solution and place it in a reactor for hydrothermal reaction at a temperature of 180° C. for 15 hours. The reaction product is washed with deionized water until it is neutral and dried. The phosphoric acid solution is obtained by diluting 85 wt % concentrated phosphoric acid with water, wherein the volume usage of 85 wt % concentrated phosphoric acid in the phosphoric acid solution accounts for 10%; Step 2: calcining the product after drying in step 1 in a tubular furnace at a temperature of 500-800° C. in an inert atmosphere, and obtaining a phosphoric acid-doped modified cathode material after cooling; Step 3: mixing hydroxylated carbon nanotubes, a binder polytetrafluoroethylene emulsion and a solvent to obtain a dispersion; the mass ratio of the hydroxylated carbon nanotubes to the binder is 1:4; Step 4: immersing the phosphoric acid-doped modified cathode material obtained in step 2 in the dispersion obtained in step 3, and drying the material after sufficient immersion; Step 5: The product after the drying treatment in step 4 is calcined, and after cooling, the electro-Fenton cathode material modified by phosphoric acid and hydroxylated carbon nanotubes is obtained.
2. The method for treating COD and chromaticity in printing and dyeing wastewater using the electro-Fenton process according to claim 1, characterized in that: In step 1, the ratio of the activated carbon fiber felt deposition area to the volume of the phosphoric acid solution is 70-80 cm 2 :50 mL.
3. The method for treating COD and chromaticity in printing and dyeing wastewater using the electro-Fenton process according to claim 1, characterized in that: In step 2, the calcination temperature in the tubular furnace is 700° C., and the calcination time in the tubular furnace is 2 to 3 hours.
4. The method for treating COD and chromaticity in printing and dyeing wastewater using the electro-Fenton process according to claim 1, characterized in that: In step 3: The solvent is a mixed solution of water and isopropanol; in the solvent, the volume ratio of water to isopropanol is 10:0.5-2; The ratio of the mass of the hydroxylated carbon nanotubes to the volume of the solvent is 1 g:10-12 mL.
5. The method for treating COD and chromaticity in printing and dyeing wastewater using an electro-Fenton process according to claim 1 or 4, characterized in that: In step 4, the ratio of the mass of the hydroxylated carbon nanotubes in the dispersion to the deposited area of the activated carbon fiber felt in the phosphoric acid-doped modified cathode material is 7-21 mg:1 cm 2 .
6. The method for treating COD and chromaticity in printing and dyeing wastewater using the electro-Fenton process according to claim 1, characterized in that: In step 5, the calcination temperature is 220-420° C., the calcination time is 1-2 hours, and the calcination atmosphere is air.
Citation Information
Patent Citations
Preparation and application of an electro-Fenton cathode material based on supported activated carbon fiber
CN107601624B
Preparation method and application of graphite felt loaded coconut shell charcoal electro-Fenton cathode material
CN117800455A
Preparation method of carbon felt loaded hydroxylated carbon nanotube cathode material as well as product and application of carbon felt loaded hydroxylated carbon nanotube cathode material
CN117756233A